Kinetics of Fading of Acid Dyes by Sodium Hydroxide in Presence of Surfactants - PATEL, M.S.; KOTHWALA, D.M.; NAGAR, T.N. (Asian Journal of Chemistry, 2010)
Cationic micelles of cetyl trimethyl ammonium bromide (C16TABr) increase the rate of reaction of acid dyes with the hydroxide ion. Non-ionic surfactant micelles Triton X-102 have also little enhancing effect, whereas the anionic micelles of sodium dodecyl sulfate (SDS) inhibit the rate. The thermodynamic parameters have been calculated in absence and presence of surfactant solutions.